Chilling Prospects: An Essay on the Economic Implications of Climate Change in Fjord Norway - Butt, Junaid Sattar; Kousar, Farzana (EuroEconomica, 2024)
Climate change poses unprecedented challenges, particularly for regions like Fjord Norway, where natural beauty and environmental resources underpin economic vitality. This essay delves into the chilling prospects of climate-induced transformations in this iconic region, offering an incisive analysis of how rising temperatures, melting glaciers, and volatile weather patterns disrupt key industries such as tourism, fisheries, and agriculture. By blending economic theory with empirical data, the essay highlights both the immediate and long-term consequences of climate change on regional GDP, employment, and trade. Furthermore, the study explores innovative adaptation strategies and policy interventions that can mitigate these impacts while fostering sustainable growth. With its focus on a region emblematic of global environmental challenges, this essay contributes to the urgent discourse on balancing economic resilience with ecological preservation.